2018
DOI: 10.1111/odi.12854
|View full text |Cite
|
Sign up to set email alerts
|

Pain after root canal treatment with different instruments: A systematic review and meta‐analysis

Abstract: The aims of this systematic review were to compare the incidence and intensity of postoperative pain after single-visit root canal treatment using manual, rotary, and reciprocating instruments. An extensive literature search in PubMed, EMBASE, Cochrane Library, and Web of Science was performed to identify investigations that evaluated the effects of different instruments on postendodontic pain. Meta-analyses and additional analyses, including subgroup and sensitivity analyses, were conducted. We included seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 35 publications
2
28
0
7
Order By: Relevance
“…In the present study, no significant differences were noted between the instruments tested (p > 0.05), and the obtained mean values were in the low range compared with previous studies using a variety of different NiTi instruments [9,18,19]. In general, the present results are corroborated by a recent meta-analysis on debris extrusion [9], and also indirectly by two meta-analyses focusing on the incidence of post-endodontic pain [11,12], as all these meta-analyses revealed that there is obviously a trend that rotary root canal preparation is associated with a reduced amount of apical debris extrusion. However, it must be confessed that direct comparisons of amounts of extruded debris are limited due to a major diversity of the experimental setups used.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, no significant differences were noted between the instruments tested (p > 0.05), and the obtained mean values were in the low range compared with previous studies using a variety of different NiTi instruments [9,18,19]. In general, the present results are corroborated by a recent meta-analysis on debris extrusion [9], and also indirectly by two meta-analyses focusing on the incidence of post-endodontic pain [11,12], as all these meta-analyses revealed that there is obviously a trend that rotary root canal preparation is associated with a reduced amount of apical debris extrusion. However, it must be confessed that direct comparisons of amounts of extruded debris are limited due to a major diversity of the experimental setups used.…”
Section: Discussionsupporting
confidence: 84%
“…In the periradicular tissues, extruded debris may cause expression of Substance P and Calcitonin gene-related peptide, which results in post-endodontic pain and in a reduced quality of life [9,10]. Evidence provided by two meta-analyses suggests that the kinematic of the instruments' motion during root canal preparation has an impact on the intensity and duration of post-endodontic pain, whereby instruments used in a rotary motion caused less pain than those used in a reciprocation motion [11,12]. The prevalence of post-endodontic pain ranges between 40% (24 h after root canal preparation) and 12% (48 h after root canal preparation), respectively [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the groups was attributed to extrusion of debris, occurring depending on the instrumentation method. 7,20,21 Previous studies showed that one of the most important reasons for postoperative pain is the extrusion of debris in the canal from the tip of the root during chemomechanical preparation, and that this would cause peripheral sensitivity characterized by hyperalgesia and spontaneous pain. 6,22 It was determined in the in vitro studies that, compared to the rotary file systems, the reciprocal file systems might cause higher amount of debris extrusion as a result of the reverse motion of instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The authors further investigated difference in pain degree between two types of instruments and found that rotary instruments were associated with lower incidence of moderate and severe postoperative pain while reciprocating instruments were associated with higher incidence of mild postoperative pain. Sun et al 16 compared incidence and intensity of postoperative pain between hand and rotary instruments, as well as between rotary and reciprocating instruments in single visit root canal treatment. According to review and metaanalysis results multiple rotary instruments contributed to significantly lower incidence and intensity of postoperative pain in comparison to hand files.…”
Section: Instrumentationmentioning
confidence: 99%